Marine bacterial community structure resilience to changes in protist predation under phytoplankton bloom conditions - Baltar, Federico; Palovaara, Joakim; Unrein, Fernando; Catala, Philippe; Horňák, Karel; Šimek, Karel; Vaqué, Dolors; Massana, Ramon; Gasol, Josep M; Pinhassi, Jarone (The ISME journal, 2016)
To test whether protist grazing selectively affects the composition of aquatic bacterial communities, we combined high-throughput sequencing to determine bacterial community composition with analyses of grazing rates, protist and bacterial abundances and bacterial cell sizes and physiological states in a mesocosm experiment in which nutrients were added to stimulate a phytoplankton bloom. A large variability was observed in the abundances of bacteria (from 0.7 to 2.4 × 10(6) cells per ml), heterotrophic nanoflagellates (from 0.063 to 2.7 × 10(4) cells per ml) and ciliates (from 100 to 3000 cells per l) during the experiment (∼3-, 45- and 30-fold, respectively), as well as in bulk grazing rates (from 1 to 13 × 10(6) bacteria per ml per day) and bacterial production (from 3 to 379 μg per C l per day) (1 and 2 orders of magnitude, respectively). However, these strong changes in predation pressure did not induce comparable responses in bacterial community composition, indicating that bacterial community structure was resilient to changes in protist predation pressure. Overall, our results indicate that peaks in protist predation (at least those associated with phytoplankton blooms) do not necessarily trigger substantial changes in the composition of coastal marine bacterioplankton communities.
Keywords: Phytoplankton; fytoplankton; Biodiversity; Heterotrophic Processes; Eukaryota; Bacteria; biodiverzita; heterotrofní procesy